PD-L1 expression and T cells infiltration in patients with uncommon EGFR-mutant non-small cell lung cancer and the response to immunotherapy. (April 2020) - Chen, Kaiyan; Cheng, Guoping; Zhang, Fanrong; Zhu, Guanxia; Xu, Yanjun; Yu, Xiaoqing; Huang, Zhiyu; Fan, Yun
Highlights: The tumor immune microenvironment in uncommon EGFR -mutated NSCLC was determined. Uncommon EGFR -mutant tumors had a high frequency of PD-L1 and CD8 dual positivity. Uncommon EGFR -mutated NSCLC had preliminary therapeutic sensitivity to PD-1 blockade. Abstract: Objectives: The efficacy of immunotherapy in epidermal growth factor receptor (EGFR) -activating non-small cell lung cancer (NSCLC) is limited. However, a series of patients with uncommon EGFR alterations was reported to derive clinical benefit from PD-1 blockade. To characterize the tumor immune microenvironment, we retrospectively evaluated tumor PD-L1 expression and T cells infiltration among NSCLC patients with uncommon EGFR mutations. Materials and methods: Immunohistochemistry was used to analyze the expression of PD-L1 and the abundance of CD4+ and CD8+ tumor-infiltrating lymphocytes (TILs). Chi-square test and Cox proportional hazards regression were conducted to investigate the correlations between the immune microenvironment features and clinicopathological variables and survival, as well as to explore the potential of immunotherapy in this patient population. Results: Among 600 NSCLC patients with EGFR alterations, we identified 49 (8.2 %) bearing uncommon mutations, including G719X, L861Q, S768I, and Ex20 ins. In total, 49.0 % (24/49) of these patients showed positive PD-L1 expression in tumor cells, markedly higher than the proportion in patients with classic sensitive mutations (19del and L858R, 12.2 % [67/551], P < 0.05). Furthermore, PD-L1 expression was associated with relatively short overall survival (OS; 15.2 vs 29.3 months, P = 0.006) and was identified as an independent predictor of OS (hazard ratio=2.57, 95 % confidence interval: 1.03–7.12, P = 0.045). Additionally, PD-L1 positivity was predominantly observed among tumors with CD8+ TILs infiltration ( P = 0.001). Uncommon EGFR -mutant tumors had a high frequency (36.7 %) of concurrent PD-L1 expression and abundant CD8 + TILs infiltration. Moreover, this dual-positive group exhibited the most unfavorable prognosis ( P = 0.023). Notably, patients with PD-L1 and CD8 dual positivity showed a favorable response to PD-1 inhibitors. Conclusions: High rates of concomitant PD-L1 expression and CD8 + TILs within the tumor microenvironment were observed in NSCLC patients with uncommon EGFR mutations. Further investigations are needed to confirm the therapeutic sensitivity to PD-1 blockade in this subgroup.